I didn't do it a book about telling the truth - Graves, Sue; Guicciardini, Desideria (London Franklin watts, 2015)
Poppy doesn't always tell the truth at home. She doesn't always tell the truth at school either. Now she's getting other children into trouble. Can she learn that it's better to own up than to tell a lie? This series introduces young children to different aspects of our emotions and behaviour. A fictional story is backed up by suggestions for activities and ideas to talk about, while a wordless storyboard encourages children to tell another story
Education
Keywords: Educational psychology